2022
DOI: 10.1021/acs.inorgchem.2c03064
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics and Strong Two-Photon Absorption Properties of Nonplanar β-Functionalized “Push–Pull” Copper Corroles with a Mixed Substituent Pattern

Abstract: A new series of nonplanar and unsymmetrically βfunctionalized "push−pull" copper corroles, CuTPC(CHO)R 7 [R = H, Br, Ph, Me, or 2-thienyl (Th)], were synthesized and characterized to elucidate the effect of β-functionalization and nonplanarity on the photophysical, redox, and nonlinear optical (NLO) properties on the corrole ring. The synthetic route to unsymmetrically β-octasubstituted copper corroles includes bromination of CuTPC(CHO) to get CuTPC(CHO)Br 7 in 80% yield, which was further subjected to the Pd-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Corroles are a pivotal class of trianionic ligands that generate stable metallocorroles with a range of metal ions in formally high oxidation states. Metallocorroles are diverse in terms of structural and redox properties and exhibit enhanced chemical as well as thermal stability along with strong absorption in the visible spectral range. Metallocorroles are very useful in dye-sensitized solar cells, , catalysis, PDT, , chemical sensors, , and nonlinear optics , because of their customizable excitation and emission spectral features. …”
Section: Introductionmentioning
confidence: 99%
“…Corroles are a pivotal class of trianionic ligands that generate stable metallocorroles with a range of metal ions in formally high oxidation states. Metallocorroles are diverse in terms of structural and redox properties and exhibit enhanced chemical as well as thermal stability along with strong absorption in the visible spectral range. Metallocorroles are very useful in dye-sensitized solar cells, , catalysis, PDT, , chemical sensors, , and nonlinear optics , because of their customizable excitation and emission spectral features. …”
Section: Introductionmentioning
confidence: 99%
“…Apart from their sensitive electronic configuration, corroles exhibit very high structural diversity, unique coordination chemistry, and strong light absorption/emission properties in comparison to porphyrins. A judiciously selected functionalization of the corrole ring’s periphery can change not only the molecule’s electronic properties, redox potentials, and coordination chemistry , but also lead to new possibilities in the areas of nonlinear optics, , near-infrared phosphorescence, catalysis, and fluorescence. , In addition to these areas of research, corrole macrocycles are good prospects for a range of sensing material applications due to their distinctive optical characteristics and synthetic adaptability. , In fact, the unusual behavior, reactivity, and high acidity of corrole imino protons have been utilized for the sensing of basic anions like CN – , F – , OAc – , and H 2 PO 4 – ions through an anion-induced deprotonation mechanism . Lodeiro and co-workers have investigated several gallium­(III) corroles for sensing toxic cyanide and fluoride anions, , while Gros and co-workers developed cobalt corrole-based porous organic polymers (POPs) for selective CO adsorption .…”
Section: Introductionmentioning
confidence: 99%
“…11 Apart from their sensitive electronic configuration, corroles exhibit very high structural diversity, unique coordination chemistry, and strong light absorption/emission properties in comparison to porphyrins. 20−23 A judiciously selected functionalization of the corrole ring's periphery can change not only the molecule's electronic properties, redox potentials, and coordination chemistry 24,25 but also lead to new possibilities in the areas of nonlinear optics, 26,27 near-infrared phosphorescence, 28−34 catalysis, 35−38 and fluorescence. 39,40 In addition to these areas of research, corrole macrocycles are good prospects for a range of sensing material applications due to their distinctive optical characteristics and synthetic adaptability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Corroles are less explored in the areas of photonics and photocatalysis and have shown promising properties. Kar and co-workers developed NIR-emissive β-tetrathiocyano functionalized corrole-based dyes via a photocatalytic pathway in good yields. Our strategy is to synthesize a novel β-functionalized corrole with strong π-acceptor groups such as dicyanovinyl (DCV) and dicyanobutadienyl (DCBD), resulting in perturbation of the Soret and Q bands in the absorption spectrum. The recent literature on corroles revealed that π-extended corroles exhibit tunable photophysical and electrochemical redox properties. For example, copper corroles demonstrate hypercorrole spectra, and the Soret band contains more than one electronic transition with significant phenyl-Cu­(d x 2 –y 2 ) charge-transfer characteristics. , Gros et al have shown ligand-to-ligand charge transfer interactions in biscyano cobalt corroles to meso -NO 2 Ph groups .…”
Section: Introductionmentioning
confidence: 99%